Preparation and diagnosis of Xerogel nanocomposites And Studying Their Effect on TNF-? Level before and after Loading Dexamethason in Male White Rats Induced Rheumatoid Arthritis - Kiaser Abdulsajjad M.Hussain 1 , Ayser Ashour Khalaf 2 , Batool Abbas hussien 1 (Institute of Medico-legal Publications Pvt Ltd, 2020)
The current study aimed to evaluate the mechanism of reducing the effect of (RA) after it was induced inmale white rat with a Complete Freund’s Adjuvant (CFA) at TNF-? level by treating Xerogel Nanoparticlesand dexamethasone nanocompounded (Xerogel / Dexa) . The free Xerogel nanoparticle had a surfaceroughness coefficient of 0.327 nm and the total percentage of volumes was 90% less than 130 nm, and theresults also indicated that induced rheumatoid arthritis causes Significant increase (p <0.05) in the meanconcentration of neoplastic necrosis factor (TNF-?) in the blood serum of male white rats, as they reacheda concentration level (10.68 ± 461.80) Pg / ml in the positive control group (G2) for six weeks of treatmentcompared with the negative control group G1)), as the concentration level in it reached (69.97±0.88) Pg /ml for the same period, and there was also a significant decrease (P <0.05) in the level of concentration ofTNF-? among members of the G5 group treated with the Xerogel / Dexa nanoparticle, as this concentrationreached (182.98 ± 6.99 ) Pg / ml compared to the positive control groups (G2) treated with the free Xerogel(G3) and the group treated with free Dexa (G4) for a six-week treatment period in these groups as theseconcentrations reached (461.80± 10.68, 483.74± 3.59, 300.32± 4.03) Pg / ml, respectively